Analisis Kalimat Perundungan dalam Film Die Welle - Ruth Saida Pangaribuan; Tanti Kurnia Sari (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
The objective of this study was to identify the forms of bullying sentences in the film "Die Welle" and to analyze the meaning of these sentences based on the theory of critical discourse analysis by Teun A. van Dijk. A descriptive qualitative method was employed in this study, with data consisting of 18 sentences containing elements of bullying found in the film "Die Welle." The analysis was carried out by identifying themes, narrative structures, as well as semantic, syntactic, stylistic, and rhetorical elements in each sentence. As a result of the analysis, three main forms of bullying sentences were identified: (1) direct verbal insults in 12 sentences or 66.7%; (2) physical threats in 5 sentences or 27.8%; and (3) emotional outbursts in 1 sentence or 5.5%. Based on van Dijk's theory, it was found that the bullying sentences in this film not only represent verbal aggression but also reflect the use of language as a tool of power and dominance within group dynamics. Thus, the film "Die Welle" demonstrates that bullying is not merely an individual act but also part of a social structure that is formed and sustained through discursive practices.